Cross-Neutralizing Antibodies to Pandemic 2009 H1N1 and Recent Seasonal H1N1 Influenza A Strains Influenced by a Mutation in Hemagglutinin Subunit 2 - Wang, Wei; Anderson, Christine M.; De Feo, Christopher J.; Zhuang, Min; Yang, Hong; Vassell, Russell; Xie, Hang; Ye, Zhiping; Scott, Dorothy; Weiss, Carol D. (PLoS pathogens, 2011)
Pandemic 2009 H1N1 influenza A virus (2009 H1N1) differs from H1N1 strains that circulated in the past 50 years, but resembles the A/New Jersey/1976 H1N1 strain used in the 1976 swine influenza vaccine. We investigated whether sera from persons immunized with the 1976 swine influenza or recent seasonal influenza vaccines, or both, neutralize 2009 H1N1. Using retroviral pseudovirions bearing hemagglutinins on their surface (HA-pseudotypes), we found that 77% of the sera collected in 1976 after immunization with the A/New Jersey/1976 H1N1 swine influenza vaccine neutralized 2009 H1N1. Forty five percent also neutralized A/New Caledonia/20/1999 H1N1, a strain used in seasonal influenza vaccines during the 2000/01-2006/07 seasons. Among adults aged 48-64 who received the swine influenza vaccine in 1976 and recent seasonal influenza vaccines during the 2004/05-2008/09 seasons, 83% had sera that neutralized 2009 H1N1. However, 68% of age-matched subjects who received the same seasonal influenza vaccines, but did not receive the 1976 swine influenza vaccine, also had sera that neutralized 2009 H1N1. Sera from both 1976 and contemporary cohorts frequently had cross-neutralizing antibodies to 2009 H1N1 and A/New Caledonia/20/1999 that mapped to hemagglutinin subunit 2 (HA2). A conservative mutation in HA2 corresponding to a residue in the A/Solomon Islands/3/2006 and A/Brisbane/59/2007 H1N1 strains that circulated in the 2006/07 and 2007/08 influenza seasons, respectively, abrogated this neutralization. These findings highlight a cross-neutralization determinant influenced by a point mutation in HA2 and suggest that HA2 may be evolving under direct or indirect immune pressure.